2012
DOI: 10.1002/jsfa.5887
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐obesity and hypolipidemic effects of Fuzhuan brick tea water extract in high‐fat diet‐induced obese rats

Abstract: Our study demonstrates that FTEs have anti-obesity and hypolipidemic functions, suggesting that it might be effective for treatment of obesity and hyperlipemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 43 publications
8
76
0
Order By: Relevance
“…pork belly oil) increased the accumulation of abdominal fat in animals, leading to body weight gain (Melhorn et al ., ; Houston et al ., ). The weight of fat tissue is significantly affected by changes in the number and size of adipocytes, and increased adipocyte size is a major factor for increasing the weight of fat tissue (Li et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…pork belly oil) increased the accumulation of abdominal fat in animals, leading to body weight gain (Melhorn et al ., ; Houston et al ., ). The weight of fat tissue is significantly affected by changes in the number and size of adipocytes, and increased adipocyte size is a major factor for increasing the weight of fat tissue (Li et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In recent years, a growing body of animal and human studies showed that dietary supplementation with tea was a potentially viable nutritional strategy for the prevention of obesity . It has been demonstrated that FBT and KDC consumption could prevent weight gain and metabolic disorders induced by HFD feeding . Furthermore, Lactobacillus johnsonii and another Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Kudingcha (KDC) from Ilex kudingcha is a popular herb beverage alternative to Camellia tea in Eastern and Southeastern Asia . KDC and Fuzhuan brick tea (FBT) are two of the most popular herb beverages with the reputation of antiobesity in China, and the preventive and therapeutic roles in metabolic disorders have been demonstrated . Polyphenols and polysaccharides are considered as the main functional ingredients in tea and KDC, which contribute to the most of the observed beneficial effects .…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown that Fuzhuan tea has a distinct chemical profile from green teas, novel phytochemical compounds , and can lower plasma lipid levels in humans with elevated LDL cholesterol . In high fat diet‐fed rats, Fuzhuan tea reduced body weight and hepatic steatosis, and suppressed development of hypolipidemia . Another study demonstrated that rats consuming Fuzhuan tea with HFD showed protein expression consistent with reduced lipogenesis and enhanced β‐oxidation, tricarboxylic acid cycle, and electron transport when compared with HFD‐fed rats not receiving the tea .…”
Section: Introductionmentioning
confidence: 96%